Peran Modal Sosial dalam Pendidikan Pesantren di Era Society 5.0 - Miya Nurohmah; Hari Subiyantoro; Imam Sukwatus Suja’i (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
Change are grew rapidly. The technological era in the industrial era 4.0 supports these changes. However, this era caused panic among people who thought that this era caused a lot of use of technology to achieve prosperity and a lack of use of human resources. The era of society 5.0 is different from that era where technology is considered not the main factor, but human resources as the main factor supporting prosperity, technology plays a role as a supporter. This research is conducted in Islamic boarding schools in East Java, where the pesantren is a unique part of society. This study aims to describe the role of Social Bounding, Social Bridging and Social Linking in Islamic boarding schools and to find out how this can increase the Value Economy of students as part of society in facing the era of society 5.0. By using a qualitative research method descriptive study, it can be seen that social bounding has different characteristics from what Woolcock suggests, namely by planting values, culture, perceptions and traditions from religious sources, state law, and instilling the Pancasila ideology. Social bridging does not have a significant difference, namely by improving community weaknesses and maximizing potential. Likewise social linking with the use of networks to help achieve goals. Meanwhile, in relation to creating a value economy in the future, skills training through extra activities are needed. Therefore, it is necessary to increase the capacity of the teaching staff so that they are able to innovate for development